Development of Regulations And Procedures And Constraints In The Process of Criminal Procedures In The Corona Virus Pandemic (Covid-19) - Didit Agung Nugroho; Denny Iswanto; Masrun; Oula Dewi Nurlaily (Faculty of Law, Merdeka University Surabaya, 2021)
The first case of Covid-19 was in March 2020, the government continues to make efforts to take mitigative steps and handle them as optimally as possible so that this virus does not spread further and brings fatalities. Various policy options were adopted to block the rate of spread, starting from the application of physical distancing, to Large-Scale Social Restrictions in various areas mapped as the epicenter of the spread. The impact of the COVID-19 corona virus pandemic has changed the pattern of human life from conventional to online. This also occurs in the criminal court trial process in Indonesia, with the issuance of Supreme Court Regulation Number 4 of 2020 concerning Administration and Trial of Criminal Cases in Electronic Courts (online criminal court) so that criminal proceedings were initially conducted face-to-face but are now being carried out online / electronically. With this writing, it is hoped that it can provide benefits to legal practitioners and the general public regarding the mechanisms for online / electronic criminal case proceedings. The research method used is a normative juridical approach to legislation and a conceptual approach. Supreme Court Regulation Number 4 of 2020 concerning Administration and Trial of Criminal Cases in Electronic Court (online criminal trial) guarantees the proceedings of the case without being constrained by forced or emergency situations so that it can better ensure the rights of the defendant with due process of law certainty laws are fulfilled. Since the holding of an electronic criminal trial, several obstacles have been identified, particularly regarding the uneven and unstable internet connection throughout Indonesia; the ability and knowledge of court officials of electronic trial support technology; as well as the uneven court equipment and equipment with adequate technology that can support the holding of electronic trials. Advocates and legal aid organizations also voiced objections to the existence of regulations that allow defendants to attend electronic hearings without being accompanied by lawyers, as well as questioning how the guarantee of fulfilling the right to a fair trial can be adopted in electronic trials.